IMMUNOTHERAPY AS NOVEL TREATMENT OF LUNG CANCER: A SYSTEMATIC REVIEW - HOSSAIN, CHOWDHURY MOBASWAR; MAITRA, SUBARNAREKHA; LYLE, NAZMUN; GERA, MEETA; PAUL, SOUVIK; DUTTA, DISHARI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Lung cancer is the top cause of cancer-related fatalities in both men and women around the world, and the second most commonly diagnosed cancer in both men and women. For many patients, traditional chemotherapy (CT) fails to give long-term benefit. Moreover, newer medicines targeting activating mutations in EGFR or ALK have shown increased response rates over CT in the minority of patients with these mutations; however, the majority of patients do not have actionable mutations and will not benefit from targeted therapies. In addition, several combinations of chemotherapeutic medicines with the angiogenesis inhibitor bevacizumab have provided only minor additional benefits. However, immunotherapy using checkpoint inhibitors has shown to have a lot of potential in the treatment of advanced non-SCLC (NSCLC) in recent trials. These new medications encourage the host immune system to recognize tumor cells as foreign invaders and halting their growth. They help alleviate immune system suppression, which allows tumor development to be tolerated. In checkpoint immunotherapy, humanized monoclonal antibodies targeting checkpoint signals such as programmed cell death receptor (PD-1) and programmed cell death ligand are employed (PD-L1). The immune system can be triggered to fight the tumor by inhibiting these receptors and signals. Immunotherapy for advanced lung cancer has created a new paradigm of therapeutic options, with increased survival and response rates and a less severe but distinct side profile when compared to CT. The PD-1 inhibitors nivolumab and pembrolizumab, as well as the PD-L1 inhibitor atezolizumab, have been approved by regulatory authorities for the treatment of advanced NSCLC. Hence, the current review article focuses on the role of immunotherapy, newer agents used for checkpoint inhibitors in lung cancer, their epidemiology, risk factors, side-effect profiles, therapeutic indications, and their mechanism of action for the successful treatment of lung cancer.